Pengaruh Kompensasi dan Beban Kerja Terhadap Kepuasan Kerja dalam Meningkatkan Kinerja Karyawan PT. Kepsindo Indra Utama Padang - Rika Wahyuni; Hadi Irfani (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to analyze how compensation and workload effect on job satisfaction; compensation and workload effect on employee performance; and job satisfaction effect on employee’s performance at the PT. Kepsindo Indra Utama Padang. Type of this research is quantitative research. The samples are 80 employees of the PT. Kepsindo Indra Utama Padang using saturation sampling technique. Methods of data collection is using questionnaire. This research is using path analysis. The results showed that: 1) compensation has positive and significant impact on job satisfaction, 2) workload have negative and significant impact on job satisfaction, 3) compensation has positive and significant impact on employee performance, 4) workload has negative and significant impact on employee performance, and 5) job satisfaction has positive and significant impact on employee performance. The results showed that the direct path of job compensation has the most powerful effect on employee performance demonstrated by having the highest impact regression coefficient (dominant) amounted to 0,664.